A kind of aging-resistant asphalt-based material and preparation method thereof

By performing organic molecular intercalation treatment on zirconium phosphate, the problem of asphalt materials aging under ultraviolet irradiation is solved, which significantly improves its anti-ultraviolet aging performance and storage stability, and extends the service life of asphalt pavement.

CN119101368BActive Publication Date: 2025-04-15BEIJING UNIV OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411379717.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-15
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing asphalt materials are prone to aging under high-energy ultraviolet irradiation, resulting in a decrease in their low-temperature crack resistance and fatigue resistance, and the road surface is prone to ruts, pits and peeling.

Method used

The intercalation treatment of zirconium phosphate by organic molecules expands the spacing between zirconium phosphate, improves its compatibility with asphalt, and improves its absorption performance to ultraviolet rays, thereby being applied to asphalt anti-aging modification.

Benefits of technology

It significantly improves the UV aging resistance of modified asphalt, extends the service life of asphalt pavement, and improves its storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119101368B_ABST
    Figure CN119101368B_ABST
Patent Text Reader

Abstract

The invention discloses an anti-aging asphalt-based material and a preparation method thereof, which belongs to the technical field of asphalt material preparation, and comprises the following raw materials by weight: 100 parts of base asphalt and 2-10 parts of an organic zirconium phosphate modifier. The invention intercalates zirconium phosphate with organic molecules to expand the interlayer spacing of zirconium phosphate, effectively avoids agglomeration between zirconium phosphate particles, improves its compatibility with asphalt, and greatly improves its absorption performance of ultraviolet rays. It is applied to asphalt anti-aging modification, and can further effectively improve the anti-ultraviolet aging performance of the obtained modified asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of asphalt material preparation, and in particular relates to an aging-resistant asphalt-based material and a preparation method thereof. Background Art

[0002] Asphalt pavement is widely used due to its good flatness, short construction period and easy maintenance. However, asphalt is an organic material and is easily aged by natural environmental factors such as light, oxygen and heat. Especially under high-energy ultraviolet rays, some chemical bonds in the asphalt molecules break, making the asphalt hard and brittle, resulting in a gradual decrease in the low-temperature crack resistance and fatigue resistance of the asphalt mixture. The road surface is prone to rutting, potholes and peeling, which seriously affect driving comfort and safety.

[0003] Adding modifiers to modify asphalt is one of the effective ways to improve the asphalt's resistance to UV aging. In previous studies, adding some layered inorganic substances to asphalt can effectively improve the asphalt's resistance to UV aging, such as magnesium-aluminum-based layered double hydroxide, montmorillonite, vermiculite, etc. However, further research is still needed to reduce the agglomeration of inorganic particles and improve the compatibility of layered inorganic substances with asphalt. In addition to the above-mentioned layered inorganic substances, zirconium phosphate has a typical layered structure, in which zirconium atoms and phosphate ions are alternately arranged to form a stable layered structure, which is conducive to the material's absorption of ultraviolet radiation. At present, there are few reports on the application of zirconium phosphate to asphalt to improve the performance of asphalt. Summary of the invention

[0004] The purpose of the present invention is to provide an aging-resistant asphalt-based material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The present invention intercalates zirconium phosphate with organic molecules to expand the interlayer spacing of zirconium phosphate, which can effectively avoid the agglomeration of zirconium phosphate particles, improve its compatibility with asphalt, and greatly improve its ultraviolet absorption performance. It is applied to asphalt anti-aging modification, which can further effectively improve the anti-ultraviolet aging performance of the obtained modified asphalt.

[0005] One of the technical solutions provided by the present invention:

[0006] An aging-resistant asphalt-based material comprises the following raw materials, measured by weight: 100 parts of base asphalt and 2-10 parts of an organic zirconium phosphate modifier.

[0007] Preferably, the matrix asphalt is road petroleum asphalt. 70# asphalt has relatively stable chemical properties, moderate viscosity, and large market supply, and 70# asphalt is preferred.

[0008] Preferably, the organic zirconium phosphate modifier is prepared by intercalating zirconium phosphate with organic molecules.

[0009] The present invention performs intercalation treatment on zirconium phosphate through organic molecules, thereby expanding the interlayer distance of zirconium phosphate, and improving the problem that zirconium phosphate, as a small-particle layered inorganic substance, is easy to agglomerate and has poor compatibility with asphalt.

[0010] Preferably, the zirconium phosphate is α zirconium phosphate or γ zirconium phosphate, among which α zirconium phosphate has better thermal stability and chemical stability, so α zirconium phosphate is more preferred.

[0011] More preferably, the intercalation treatment comprises the following steps: adding the organic molecule and the zirconium phosphate into distilled water, controlling the liquid-to-solid ratio, ultrasonicating, centrifuging, washing, filtering, and vacuum drying to constant weight.

[0012] More preferably, the organic molecule is selected from organic amines or long carbon chain quaternary ammonium salts; organic amine molecules are easier to intercalate, and the organic molecule is preferably an organic amine; the organic amine is one or more of monoamines, diamines and polyamines; preferably N-isopropyl-N'-phenyl-p-phenylenediamine.

[0013] N-isopropyl-N'-phenyl-p-phenylenediamine contains a hindered amine structure. Under the synergistic effect of layered inorganic zirconium phosphate and hindered amine structure, the absorption capacity of ultraviolet rays can be greatly improved. Applying organic zirconium phosphate modifier to asphalt anti-aging modification can significantly improve the anti-ultraviolet aging performance of asphalt.

[0014] Preferably, the molar ratio of the organic molecule to zirconium phosphate is 1:(0.5-2).

[0015] If the dosage of organic zirconium phosphate is too low during the asphalt preparation process, the modification effect will not be obvious, and the improvement of the asphalt's anti-ultraviolet aging performance will not be obvious; if the dosage of organic zirconium phosphate is too high, the storage stability of asphalt will be greatly reduced.

[0016] Preferably, the liquid-to-solid ratio is the ratio of the volume of distilled water to the total mass of organic molecules and zirconium phosphate, and the liquid-to-solid ratio is 100 mL / g.

[0017] Preferably, the ultrasonication time is 40-80 min.

[0018] The second technical solution provided by the present invention is:

[0019] A method for preparing the above-mentioned aging-resistant asphalt-based material comprises weighing raw materials according to a ratio, heating the asphalt to 140-170° C., adding the organic zirconium phosphate modifier, and high-speed shear stirring to prepare the aging-resistant asphalt material.

[0020] Preferably, the specific operation of the high-speed shear stirring is: stirring at a rotation speed of 4000-5000 rpm for 0.5-1 h.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] 1) The present invention inserts organic molecules into the interlayers of zirconium phosphate through intercalation treatment to obtain organic zirconium phosphate, thereby enhancing the affinity between zirconium phosphate and asphalt, improving the agglomeration of zirconium phosphate particles in asphalt, and using long-chain organic molecules for intercalation, which has a better organic effect and significantly improves its compatibility with asphalt;

[0023] 2) The present invention adds organic zirconium phosphate to ordinary road asphalt, and utilizes the multi-level chemical absorption and physical shielding effect of organic zirconium phosphate on ultraviolet rays, so that the asphalt material has excellent ultraviolet blocking effect, significantly improves the aging resistance of road asphalt, and prolongs the service life of asphalt pavement;

[0024] 3) The present invention inserts a hindered amine antioxidant into zirconium phosphate to achieve the organicization of zirconium phosphate, and can significantly improve the anti-aging ability of asphalt through the synergistic effect of the zirconium phosphate layered structure and the hindered amine structure. In addition, the zirconium phosphate layered structure can also play a certain protective role on the hindered amine antioxidant and improve the long-term effectiveness of the antioxidant. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 Schematic diagram of the intercalation modification of zirconium phosphate by organic molecules in the present invention, wherein (a) is a schematic diagram of the modification in which the organic molecules are distributed in the form of a single layer between zirconium phosphate molecules, and (b) is a schematic diagram of the modification in which the organic molecules are distributed in the form of a double layer between zirconium phosphate molecules. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] The room temperature in the present invention refers to 25±2°C.

[0033] In the embodiments of the present invention, “parts” refer to “parts by mass” unless otherwise specified.

[0034] In order to more clearly demonstrate the modification process of zirconium phosphate by organic molecules, the present invention provides Figure 1 Schematic diagram of the intercalation modification of zirconium phosphate by organic molecules in the present invention, wherein (a) is a schematic diagram of the modification in which the organic molecules are distributed between zirconium phosphate molecules in the form of a single layer, and (b) is a schematic diagram of the modification in which the organic molecules are distributed between zirconium phosphate molecules in the form of a double layer; the specific single-layer or double-layer distribution depends on the type of inserted organic molecules. In the process of intercalation of organic molecules into zirconium phosphate, if the distribution of the organic molecules between zirconium phosphate layers is known, the amount of organic molecules is determined accordingly; if the distribution of the organic molecules between zirconium phosphate layers is unknown, the amount of organic molecules required for the double-layer distribution should be added or the amount of organic molecules should be determined after a preliminary experiment to determine the distribution of the organic molecules between zirconium phosphate layers.

[0035] Example 1: A method for preparing an aging-resistant asphalt-based material

[0036] S1. Preparation of an organic zirconium phosphate modifier: Weigh zirconium phosphate and 1,12-diaminododecane at a molar ratio of 1:1, add distilled water, and control the liquid-solid ratio to 100 mL / g; ultrasonically treat at room temperature for 60 min, centrifuge the resulting reaction solution, take the precipitate, wash it with ethanol, filter it, and finally vacuum dry it to constant weight to obtain 1,12-diaminododecane intercalated zirconium phosphate;

[0037] S2. Weigh 100 parts of 70# asphalt, heat to 160°C, add 4 parts of 1,12-diaminododecane intercalated zirconium phosphate prepared in S1, and high-speed shear at 4500rpm for 60 minutes to prepare an aging-resistant asphalt-based material.

[0038] Example 2 A method for preparing an aging-resistant asphalt-based material

[0039] S1. Preparation of an organic zirconium phosphate modifier: Weigh zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine at a molar ratio of 1:1, add distilled water, and control the liquid-solid ratio to be 100 mL / g; ultrasonically treat at room temperature for 60 min, centrifuge the resulting reaction solution, take the precipitate, wash it with ethanol, filter it, and finally vacuum dry it to constant weight to obtain N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate;

[0040] S2. Weigh 100 parts of 70# asphalt, heat to 160°C, add 4 parts of N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate prepared in S1, and high-speed shear at 4500rpm for 45 minutes to prepare an aging-resistant asphalt-based material.

[0041] Example 3: Preparation method of an aging-resistant asphalt-based material

[0042] S1. Preparation of an organic zirconium phosphate modifier: Weigh zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine at a molar ratio of 1:0.5, add distilled water, and control the liquid-solid ratio to 100 mL / g; ultrasonically treat at room temperature for 40 min, centrifuge the resulting reaction solution, take the precipitate, wash it with ethanol, filter it, and finally vacuum dry it to constant weight to obtain N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate;

[0043] S2. Weigh 100 parts of 70# asphalt, heat to 160°C, add 2 parts of N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate prepared in S1, and high-speed shear at 4000rpm for 30 minutes to prepare an aging-resistant asphalt-based material.

[0044] Example 4: Preparation method of an aging-resistant asphalt-based material

[0045] S1. Preparation of an organic zirconium phosphate modifier: Weigh zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine at a molar ratio of 1:2, add distilled water, and control the liquid-solid ratio to be 100 mL / g; ultrasonically treat at room temperature for 80 min, centrifuge the resulting reaction solution, take the precipitate, wash it with ethanol, filter it, and finally vacuum dry it to constant weight to obtain N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate;

[0046] S2. Weigh 100 parts of 70# asphalt, heat to 160°C, add 10 parts of N-isopropyl-N'-phenyl-p-phenylenediamine intercalated zirconium phosphate prepared in S1, and high-speed shear at 5000rpm for 60 minutes to prepare an aging-resistant asphalt-based material.

[0047] Example 5

[0048] The same as Example 1, except that zirconium phosphate and 1,12-diaminododecane are weighed in S1 according to the molar ratio of 1:2.

[0049] Example 6

[0050] The same as Example 1, except that in S1, zirconium phosphate and 1,12-diaminododecane are weighed in a molar ratio of 1:0.5.

[0051] Comparative Example 1

[0052] Same as Example 1, except that 1 portion of 1,12-diaminododecane intercalated zirconium phosphate prepared in S1 is added to S2.

[0053] Comparative Example 2

[0054] Same as Example 1, except that 12 parts of 1,12-diaminododecane intercalated zirconium phosphate prepared in S1 were added to S2.

[0055] Comparative Example 3

[0056] 100 parts of 70# asphalt were weighed, heated to 160°C, 4 parts of zirconium phosphate were added, and high-speed shearing was performed at 4500 rpm for 60 minutes to prepare a zirconium phosphate-modified asphalt-based material.

[0057] Comparative Example 4

[0058] Same as Example 1, except that the 1,12-diaminododecane in S1 is replaced by an equal amount of ethylamine.

[0059] Comparative Example 5

[0060] Same as Example 1, except that the ultrasonic treatment in S1 was 30 min.

[0061] Comparative Example 6

[0062] Same as Example 1, except that the ultrasonic treatment in S1 was performed for 90 min.

[0063] Comparative Example 7

[0064] The same as Example 1, except that the molar ratio of zirconium phosphate to 1,12-diaminododecane in S1 is 1:2.5.

[0065] Comparative Example 8

[0066] The same as Example 1, except that the molar ratio of zirconium phosphate to 1,12-diaminododecane in S1 is 1:0.3.

[0067] In order to verify the relevant performance of the aging-resistant asphalt-based material, the above-mentioned base asphalt, the aging-resistant asphalt-based material prepared in Examples 1-4, and the modified asphalt prepared in Comparative Examples 1-7 were subjected to asphalt separation experiments according to the current industry standard "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004) to analyze the asphalt storage stability. In addition, the asphalt samples were subjected to UV aging experiments (UV intensity 800w / m 2 , temperature is 60℃, aging time is 3 days), and a dynamic shear rheometer is used to carry out temperature scanning experiments on the samples before and after aging, and the complex modulus aging index (CAI) and phase aging index (PAI) are calculated to evaluate the anti-aging ability of asphalt. The smaller the value of the complex modulus aging index and the larger the value of the phase aging index, the stronger the anti-aging ability of asphalt. The aging index calculation formula is as follows, and the measurement results are shown in Table 1.

[0068]

[0069] Where: aging represents the index after aging, and origin represents the index before aging.

[0070] Table 1 Asphalt softening point difference and rheological aging index

[0071]

[0072]

[0073] Note: The softening point difference value is the difference between the softening points of the upper and lower layers after the asphalt separation test. The larger the softening point difference value, the worse the asphalt storage stability, and the smaller the softening point difference value, the better the asphalt storage stability.

[0074] According to the experimental data recorded in Table 1, by comparing 70# base asphalt, Example 1 and Comparative Examples 1-2, it can be seen that: if the dosage of organic zirconium phosphate is too low during the asphalt preparation process, the modification effect is not obvious, and the improvement of the asphalt's anti-ultraviolet aging performance is not obvious; if the dosage of organic zirconium phosphate is too high, the storage stability of asphalt will be greatly reduced.

[0075] In Example 2, when preparing the organic zirconium phosphate modifier, zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine are mixed at a molar ratio of 1:1. In Example 3, when preparing the organic zirconium phosphate modifier, zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine are mixed at a molar ratio of 1:0.5. Since the amount of organic molecules added in Example 2 is larger than that in Example 3, more organic molecules are distributed between the molecular layers of zirconium phosphate, and the modification of zirconium phosphate is more sufficient, so that the anti-aging performance of the aging-resistant asphalt-based material prepared in Example 2 is better than that in Example 3; in Example 4, when preparing the organic zirconium phosphate modifier, zirconium phosphate and N-isopropyl-N'-phenyl-p-phenylenediamine are mixed at a molar ratio of 1:2. Compared with Example 2, the modification effect of zirconium phosphate is not greatly improved. Therefore, the anti-aging performance of the aging-resistant asphalt-based material prepared in Example 4 is equivalent to that in Example 2.

[0076] By comparing Example 1 with Comparative Example 3, it can be seen that the compatibility of zirconium phosphate and asphalt can be effectively improved by intercalating organic molecules, and the storage stability of the modified asphalt can be greatly improved; from Example 1 and Comparative Example 4, it can be seen that the use of long-chain organic molecules has a better effect.

[0077] By comparing Example 1 and Example 2, it can be seen that inserting a hindered amine antioxidant into zirconium phosphate can further improve the anti-ultraviolet aging ability of the modified asphalt while realizing the organicization of zirconium phosphate. The intercalation method adopted in Example 2 is superior to conventional organic molecule intercalation in improving the anti-ultraviolet aging ability.

[0078] By comparing Example 1 and Comparative Examples 5-6, it can be found that during the intercalation process, if the ultrasonic treatment time is too short, the organic molecules will be insufficiently intercalated, resulting in a poor asphalt modification effect; if the ultrasonic treatment time is too long, the asphalt modification effect is not further improved, so the ultrasonic treatment time should not be too long.

[0079] By comparing Example 1 with Comparative Examples 7-8, it can be found that: during the intercalation process, if the number of intercalated organic molecules is too small, the organic treatment of zirconium phosphate will be insufficient, affecting the storage stability of the modified asphalt; if the number of intercalated organic molecules is too large, the asphalt modification effect will not be further improved, and it will also cause a burden on the washing and impurity removal in the intercalation process, so the number of intercalated organic molecules should not be too large.

[0080] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An aging-resistant asphalt-based material, characterized in that: The raw materials are as follows: 100 parts of base asphalt, 4 parts of organic zirconium phosphate modifier; The preparation method of the organic zirconium phosphate modifier is as follows: zirconium phosphate and 1,12-diaminododecane are weighed according to a molar ratio of 1:1, distilled water is added, and the liquid-solid ratio is controlled to be 100 mL / g; ultrasonic treatment is performed at room temperature for 60 minutes, the obtained reaction solution is centrifuged, the precipitate is taken, and it is washed with ethanol, filtered, and finally vacuum dried to constant weight to obtain the organic zirconium phosphate modifier.

2. A method for preparing the aging-resistant asphalt-based material according to claim 1, characterized in that: The raw materials are weighed according to the ratio, the asphalt is heated to 140-170° C., the organic zirconium phosphate modifier is added, and high-speed shear stirring is performed to prepare the aging-resistant asphalt material.

Citation Information

Patent Citations

  • Method for preparing carbon nano-tube by catalyzing and carbonizing polymer and / or asphalt

    CN101214947A